Deal or no deal? Understanding entrepreneurs’ criteria and deal breaker in investor selection processes - Sturm, Tobias; Bican, Peter M.; Riar, Frederik J.; Guderian, Carsten; Welz, Tobias (Journal of Business Economics, 2024)
This study provides insights into the criteria applied by entrepreneurs in selecting venture capital investors. Building upon interviews with entrepreneurs, we outline a framework that categorizes the decision-making process into three principal criteria clusters: (1) financial aspects, with a focus on valuation; (2) value-added services; and (3) personal fit attributes. We identify key factors within these categories, such as valuation, network, expertise, reputation, empathy, trust, and the personal connection between investors and entrepreneurs, as pivotal in guiding entrepreneurs” choices for the “right” investor. Our analysis reveals the interrelatedness of these criteria, notably how they align with the valuation aspect. Entrepreneurs exhibit a readiness to accept lower valuations if compensated with enhanced value-added services. Additionally, we uncover novel insights into deal breakers within the financing, decision-making and negotiation processes. Entrepreneurs predominantly halt negotiations due to perceived unfair valuations, inadequate investor expertise, and overly rigorous control measures, including stringent reporting requirements. These findings provide a deeper understanding of the entrepreneurs’ decision-making paradigms during financing scenarios, offering valuable implications for entrepreneurs, venture capital managers, and policymakers and addressing gaps in existing research on the adverse functions of specific selection criteria.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Deal breakers; Entrepreneurial decision-making; Entrepreneurship; Selection criteria; Startup financing; Venture capital